Exploration of core motivational factors of Muslim friendly spa utilization among the spa goers / Nur Afiqah Mohamad and Nor Dalila Marican - Mohamad, Nur Afiqah; Marican, Nor Dalila (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Wellness and spa industry become a part of revenue contributor to Malaysia. To attract more traveller and local to wellness and spa industry, the motivational factor plays crucial part in determining the customer behaviour. As Muslim friendly spa has been introduced as a new type of preference for spa, a study on core motivational factors of Muslim friendly spa utilization among spa goers will be conducted. A qualitative method will be conducted that focusing on in-depth interviews 10 different spa goers with different profession and demographic. The expected result will be factors in utilization of Muslim friendly spa product and services among spa goers.